The Natural History of Postconcussion Recovery Among High School Athletes. Issue 5 (September 2019) - Dise-Lewis, Jeanne E.; Forster, Jeri E.; McAvoy, Karen; Stearns-Yoder, Kelly A.; Bahraini, Nazanin H.; Laker, Scott R.; Brenner, Lisa A.
Abstract : Objective: Evaluate postconcussive symptom reporting and recovery. Setting: Public high school. Participants: Unmatched controls ( n = 760); students who sustained a sports-related concussion ( n = 77); matched controls (gender, grade, sport) ( n = 77). Design: Prospective longitudinal cohort study. Outcome measure: Immediate Postconcussion Assessment and Cognitive Testing. Results: At baseline, athletes who went on to sustain concussions were more likely than unmatched controls to be younger ( P = .02), male ( P = .001), and participate in different sports ( P < .0001) such as football (concussed = 52%, unmatched controls = 20%). Differences were also noted regarding a previous history of concussion ( P = .045; concussed athletes = 26%; unmatched control athletes = 16%) and lifetime number of concussions ( P = .05). At baseline, those whose sustained concussions during the study period were more likely than matched controls to report numbness ( P = .01) and concentration problems ( P = .01) and more likely than unmatched controls to report dizziness ( P = .02), sensitivity to light ( P = .01), sensitivity to noise ( P = .002), and numbness ( P = .02). However, when data were reanalyzed and those with a previous history of concussion were removed, differences between those who sustained concussions during the study period and matched controls were no longer significant; when compared to unmatched controls, sensitivity to light ( P = .01) and vision problems ( P = .04) remained significant. Among those who sustained concussions, median time to recovery was 6 days (95% confidence interval: 4-9), and 71 out of 77 (92%) recovered by the fourth postinjury evaluation (median: 20 days postinjury). Conclusions: Course and time frame of recovery were variable. Data also suggest that a previous history of concussion may be contributing to baseline symptom reporting and highlight the potential enduring impact of history of concussion on sensorimotor function. However, further research as to whether preinjury measures of sensorimotor function may increase understanding regarding concussion risk is warranted.